Training and Integrating Public Service Interpreters in a Refugee Health Clinic: A Mixed-Method Approach to Evaluate an Innovative Program - Leanza, Yvan; Rocque, Rhéa; Brisset, Camille; Gagnon, Suzanne (Refuge: Canada’s Journal on Refugees, 2021)
Language barriers can harm refugees’ health, and trained interpreters are a solution to overcome these barriers in all health consultations. This study trained interpreters and integrated them in a refugee clinic. Nepali-speaking migrants were recruited and underwent 50 hours of training to serve as interpreters for recently arrived Bhutanese refugees in Quebec City. To evaluate the project, mixed data were collected. At baseline and follow-up, patients’ health (as perceived by practitioners) and satisfaction were evaluated. Interpreters and practitioners were also interviewed and took part in joint discussion workshops. Patients’ health remained stable but, interestingly, patients were slightly less satisfied at follow-up. Practitioners and interpreters described both benefits and difficulties of the program. For example, integrating interpreters within the clinical team allowed for better collaboration and mutual knowledge of cultures. Challenges included work overload, conflicts between interpreters and practitioners, and role conflicts for interpreters. Overall, the full-time integration of trained interpreters in the clinic facilitated communication and case administration. This practice could be especially beneficial for refugee clients. In future interventions, interpreter roles should be better clarified to patients and practitioners, and particular attention should be paid to selection criteria for interpreters.